Upaya Pemberdayaan Masyarakat Melalui Pelatihan Digital Marketing bagi UMKM di Desa Kutuk - Antari Ayuning Arsi; Lindu Sukma Melati; Dina Wulung Savitri; Pandu Dwi Jatmiko; Novita Laylatul Choiriyah; Julia Eka Damayanti; Hierro Nico Almayda; Siti Amatul Ulfiah; Imam Fauzi Ath Thoriq; Maftukhatul Fitriyah; Nabila Asti Sephiawardani (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2023)
An increasingly developing world has led to the emergence of the digital world, which also influences the world of marketing. Micro, Small and Medium Enterprises (MSMEs), as contributors to state revenues, need to adapt to this change. Adaptations can be made, such as digital marketing strategies. Digital marketing has been proven to have an effect on the profits received by business owners. However, there are still many MSME owners who do not have the ability to operate technology. Therefore, the need for training and assistance to MSME owners regarding digital marketing. Kutuk Village, as one of the villages in Kudus, Central Java, has several MSMEs that have the potential to develop through digital marketing. Through training and mentoring, MSME owners have the knowledge and skills related to digital marketing. The results obtained are business branding starting from logos and packaging, creating social media and creating marketplaces. MSME owners feel helped and can use the knowledge and skills they have acquired.